Kapasitas Bisnis Pemerintah Desa dalam Perspektif Business-Government Relationship Pasca Implementasi Otonomi Desa (Kasus di Kabupaten Banyumas) - Denok Kurniasih; Paulus Israwan Setyoko; M Imron (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
The Indonesian Governments policies after the implementation of village autonomy are directed to villages business development. Village governments duties and functions are not only related to administrative matters anymore, but also in operation of villages business. This shows that there is a developing business commitment in Indonesia. The research result shows that the Business-Government Relationship in Indonesia has changed from one way to mutual interaction, as shown with the development of Public Sector Entrepreneurship and business commitment in village government environment. Both factors evidently improve the capacity of business, which begins to be developed by the Indonesian Government at all levels. The development of Public Sector Entrepreneurship is shown with the business creativity, business cooperation, and professionalism of village government in governments business management. Meanwhile, local governments business commitment is shown with support of policies, funding and human resources in governments business management. Governments business capacity is shown with efficiency, effectiveness and economy (value for money) achieved by governments business unit. In Indonesia, particularly in Banyumas Regency, village autonomy has given opportunity for the development of Business-Government Relationship at local level.